2011
DOI: 10.18227/1982-8470ragro.v5i2.534
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização química e física de frutos de diferentes acessos de tomateiro em casa de vegetação

Abstract: Palavras-chaves -Germoplasma. Produção. Roraima. Solanum lycopersicon.Abstract -Tomato (Solanum lycopersicon) is cultivated on a large scale in Brazil and worldwide. Due to the fact that it has a relatively short cycle and higher yields, the tomato crop has good economic prospects and the cultivated area is increasing dayle. The aim of this study was to evaluate the physical and chemical characteristics of fruits of different tomato accessions in the greenhouse conditions in Boa Vista-RR. The following accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
0
5
1
4
Order By: Relevance
“…Morphoagronomic and physicochemical analyzes of the fruits of the 15 plants selected in this study (Table 1) are mainly characterized by their average fruit mass (58.7-99.1 g). These values were superior to the ones found by Sousa et al (2011) who, among other accessions, also evaluated cultivar Yoshimatsu in the state of Roraima, where the averages did not exceed 34.69 g. This could be explained because these authors conducted the experiment in pots, which would limit plant development.…”
Section: Individual Plant Selectioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Morphoagronomic and physicochemical analyzes of the fruits of the 15 plants selected in this study (Table 1) are mainly characterized by their average fruit mass (58.7-99.1 g). These values were superior to the ones found by Sousa et al (2011) who, among other accessions, also evaluated cultivar Yoshimatsu in the state of Roraima, where the averages did not exceed 34.69 g. This could be explained because these authors conducted the experiment in pots, which would limit plant development.…”
Section: Individual Plant Selectioncontrasting
confidence: 68%
“…Cv. Yoshimatsu has average fruit mass between 16 and 45 g (Pena et al, 2010;Sousa et al, 2011;Andrade et al, 2013). The results show that from cv.…”
Section: Progeny Testmentioning
confidence: 99%
“…The ascorbic acid contents were higher in PAB fruit than in Mascot, except when harvested turning (Table 2). Souza et al (2011) found average values of 33.83 and 42.66 mg of ascorbic acid respectively to the access 18 and 209 of cherry tomatoes harvested at the commercial maturity point. These values are close to those found in this study for PAB and Mascot.…”
Section: Longevity Of Fruit Stored At Controlled Temperature (12 °C Amentioning
confidence: 88%
“…The highest values observed at red and ripe stages may have occurred because these fruit were harvested at a stage of full maturation when compared to fruit that have completed their maturation process out of the parent plant (FERREIRA et al, 2010;SOUZA et al, 2011).…”
Section: Longevity Of Fruit Stored At Ambient Temperature (25 °C ± 2 °C)mentioning
confidence: 99%
“…Contudo, Sousa et al (2011) relataram valores entre 7,20 e 45,60 mg 100 g -1 , que podem ser encontrados, dependendo de determinados aspectos, como época do ano, luz, adubação e substrato. Os maiores valores obtidos -em torno de 18 mg 100 g -1 , no manejo CE, e no nível de 1,6 dS m -1 -podem ser explicados pela menor alocação de nitrogênio nos frutos.…”
Section: Resultsunclassified